Pineapple Liquid Waste as Nata De Pina Raw Material - Sutanto, Agus (Makara Journal of Technology, 2012)
This research aims to study the quantity, quality, ecological and economic feasibility of nata de pina production (NP) from pineapple liquid waste (PLW). The design of the study employs complete random design (CRD) with three treatments: PLW without nutrients addition (A), PLW nutrients addition (B), and PLW stored for six months with nutrients addition (C). The nata de pina’s production factors measured were weight, thickness, fiber content, color, brightness, and residual waste. The highest weight was reached in treatment B (899 grams), followed by treatment A (616.4 grams), and C (477.8 grams). The thickness of NP of the height and low as in treatment B (1.58 cm) followed by treatment A (1.24 cm) and C (0.88 cm), respectively. The highest fiber content was found in treatment C (9.3%) followed by treatment B (7.6%) and A (6.9%), respectively. The fiber content, along with color quality and brightness fit with food standards. The production of NP may reduce the volume of the PLW from 46.2% to 89.1% (p =0.001). Based on the standard value of biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS) below to the required threshold except pH. The production of NP is economically feasible to 4.7 BC ratio. The overal manufacture of nata de pina from PLW produces better and feasible product ecologically and economically